Traumatic events and posttraumatic stress symptoms in a treatment-seeking sample of Ukrainian children during the war - Elisa Pfeiffer; Maike Garbade; Cedric Sachser (BMC, 2024)
Abstract Background The Russian invasion of Ukraine resulted in a dramatic increase of children and adolescents being confronted with war and other traumatic experiences, which could result in an increase of trauma-related mental health disorders such as posttraumatic stress disorder (PTSD) in an entire generation. This study aims at reporting the prevalence of traumatic events, PTSD, and Complex PTSD (CPTSD) in children and adolescents seeking for mental health treatment since the Russian invasion. Additionally, the consistency of child and caregiver reported trauma, PTSD and CPTSD will be examined. Methods This study is part of the "TF-CBT Ukraine" project in which Ukrainian therapists were trained in assessing their patients via the "Child and Adolescent Trauma Screen" (CATS-2) before initiating trauma-focused treatment, if indicated. Altogether N = 200 Ukrainian children and adolescents (M age = 12.01, range 4-21; 62.0% female) were included in the study between October 2022 and August 2023. Data were analysed descriptively, via t-tests and bivariate correlations. Results The children and adolescents reported on average four different traumatic events, most frequently war (n = 123; 68.7%), bullying threats (n = 71; 39.7%) and domestic violence (n = 68; 38.0%). Almost 70% (n = 123) of the participants fulfilled the DSM-5 PTSD criteria, 31% (n = 56) fulfilled the ICD-11 PTSD criteria and 21% (n = 38) the ICD-11 CPTSD criteria. Rates of PTSD were even higher in preschool children (95%). The comparisons of self-and caregiver reports on traumatic events and PTSD/CPTSD severity scores indicated moderate to high correlations between the patients and their caregivers (r = 0.710-0.767). Conclusions This study shows that Ukrainian children and adolescents starting treatment report a high number of traumatic events and trauma-related symptoms, which could have a long-lasting negative impact on their social-emotional development and quality of life. The implementation of evidence-based trauma-focused interventions for these children is therefore crucial.